2018
DOI: 10.1161/circep.117.005797
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Isovolumetric Relaxation Time Is Prolonged in Fetal Long-QT Syndrome

Abstract: The LVIRT is prolonged in LQTS fetuses. Findings of a prolonged N-LVIRT and sinus bradycardia can improve the prenatal detection of fetal LQTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
1
23
1
Order By: Relevance
“…As an observational exercise, we retrospectively measured the normalized L‐IVRT (L‐IVRT/atrial cycle length × 100) via Doppler at the mitral inflow and aortic outflow during both 2:1 AV block and sinus bradycardia. As reported in Clur et al, the optimal normalized L‐IVRT cutoff value for diagnosis of LQTS at 21‐30 weeks gestational age is 14.2% (CI 11.9‐14.3%) 10 . At our patient's 22 week gestation scan in 2:1 AV block, the normalized L‐IVRT was 20% (100 msec/500 msec × 100)—well above the reported cutoff value 10 .…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…As an observational exercise, we retrospectively measured the normalized L‐IVRT (L‐IVRT/atrial cycle length × 100) via Doppler at the mitral inflow and aortic outflow during both 2:1 AV block and sinus bradycardia. As reported in Clur et al, the optimal normalized L‐IVRT cutoff value for diagnosis of LQTS at 21‐30 weeks gestational age is 14.2% (CI 11.9‐14.3%) 10 . At our patient's 22 week gestation scan in 2:1 AV block, the normalized L‐IVRT was 20% (100 msec/500 msec × 100)—well above the reported cutoff value 10 .…”
Section: Discussionsupporting
confidence: 70%
“…At our patient's 22 week gestation scan in 2:1 AV block, the normalized L‐IVRT was 20% (100 msec/500 msec × 100)—well above the reported cutoff value 10 . At the 23 week gestation scan in sinus bradycardia, the normalized L‐IVRT was 11% (50 msec/450 msec × 100)—within the reported normal range 10 . This suggests fetal L‐IVRT may correlate to fetal QT and could be monitored as maternal treatment is adjusted.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…The measurements performed in these cases, were never validated in LQTS or correlated to QT-intervals. In a recently published multinational study, it was shown that the left ventricular isovolumetric relaxation time (LVIRT) is prolonged in LQTS foetuses, even when corrected for cycle length [ 40 ]. In our study we used a validated measurement for myocardial contraction duration, as a surrogate for QT-interval, and an approximation to the combination of the left ventricular isovolumetric relaxation time, the left ventricular contraction time and the LVIRT.…”
Section: Discussionmentioning
confidence: 99%